Assessing the Viability of Orange Charcoal as an Adsorbent for the Removal of Methyl Orange Dye from Aqueous Solutions - Alhaslook, Swassy Atia; Aldeib, Mohamed Ali; Algesh, Nasser Salem (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aimed to explore the use of orange charcoal, which can be obtained at a low cost from local markets in Libya, as an effective adsorbent for the removal of Methyl Orange (MO) from aqueous solutions. The disposal of dyes into the environment, including MO, has become a global concern due to its negative impact on water resources. The study investigated the effects of various parameters such as concentration, contact time, pH, and adsorbent dosage, on the adsorption process in batch experiment at 25oC, and evaluate the adsorption efficiency, kinetics, and equilibrium isotherms associated with MO removal using activated carbon derived from orange charcoal as an adsorbent. The results showed that the orange charcoal activated with HCL was an effective adsorbent for the removal of MO, and the adsorption capacity of the adsorbent was determined using the Freundlich isotherm. The study concluded that the pseudo-second-order model was well-fitted to the experimental data. In summary, this study suggests that orange charcoal activated by HCL (OCAC) could be a useful and cost-effective method for the removal of MO from aqueous solutions.